Encouraging Asian Immigrant Women to Disclose Intimate Partner Violence in Primary Care Settings. Issue 7 (April 2022) - Tavrow, Paula; Azucar, Danny; Huynh, Dan; Yoo, Caroline; Liang, Di; Pathomrit, Wanda; Withers, Mellissa
Risks of intimate partner violence (IPV) often are higher among immigrant women, due to dependency, language barriers, deportation fears, cultural beliefs, and limited access to services. In the United States, Asian immigrant women experiencing IPV often are reluctant to disclose abuse. Viewing videos that depict IPV survivors who have successfully obtained help might encourage disclosure. After conducting formative research, we created brief videos in four Asian languages (Korean, Mandarin Chinese, Thai, and Vietnamese) for use in primary care clinic consultation rooms. We then conducted in-depth interviews with 60 Asian immigrant women in California to get their perspectives on how helpful the videos might be in achieving disclosure. Most participants believed the videos would promote disclosure in clinics, although those who had been abused seemed more skeptical. Many had stereotyped views of victims, who they felt needed to be emotive to be credible. Videos should be upbeat, highlighting the positive outcomes of escaping violence and showing clearly each step of the process. Various types of IPV should be described, so that women understand the violence is not exclusively physical. Victims would need reassurance that they will not be arrested, deported, or forced to leave their abusers. Discussing the benefits of escaping violence to children could be influential. Victims also must be convinced that providers are trustworthy, confidential, and want to help. To assist immigrant populations to disclose IPV to a health provider, videos need to be culturally relevant, explain various types of violence, allay fears, and show clear processes and benefits.